Seismic performance of a cable-stayed bridge crossing strike-slip faults. (January 2022) - Gu, Yitong; Guo, Junjun; Dang, Xinzhi; Yuan, Wancheng
Abstract: Past earthquakes demonstrated the vulnerability of bridges crossing fault ruptures, and this issue has drawn attentions of researchers and engineers. Previous studies on this topic are limited to girder bridges. In this paper, seismic performance of a three-span cable-stayed bridge subjected to strike-slip faults is investigated. Nonlinear time-history analyses are conducted using actual near-fault ground motion records, which are applied to the bridge in both fault-normal and fault-parallel directions. Seismic responses of fault-crossing and near-fault cable-stayed bridges are compared. Effects of permanent ground displacements and fault crossing angles on the response of the fault-crossing bridge are also evaluated. Results show that seismic responses of the fault-crossing bridge are larger than those of the near-fault bridge, especially the girder and bearing displacements. When the fault strike is perpendicular to the longitudinal axis of the bridge, the permanent ground displacement significantly affects the bearing displacement, but has little impact on the responses of pylons and cables. Comparing with other fault crossing angles, the pylon displacement and longitudinal bearing displacement are smaller in the case of 90°, but the transverse bearing displacement is larger.